2022
DOI: 10.3389/fphar.2022.873556
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities With Routinely Collected Data on the Utilization of Cancer Medicines. Perspectives From Health Authority Personnel Across 18 European Countries

Abstract: Background: Rising expenditure for new cancer medicines is accelerating concerns that their costs will become unsustainable for universal healthcare access. Moreover, early market access of new oncology medicines lacking appropriate clinical evaluation generates uncertainty over their cost-effectiveness and increases expenditure for unknown health gain. Patient-level data can complement clinical trials and generate better evidence on the effectiveness, safety and outcomes of these new medicines in routine care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…To control the government’s expenditure, risk-sharing arrangements can be introduced when these innovative medicines are included on the National Reimbursement Drug List, and real-world evidence can be used to monitor the medicines’ cost–effectiveness. 33 , 34 If a targeted medicine has no meaningful clinical benefits compared with essential medicines, clinical guidelines should recommend use of the latter over the former. Currently, the Chinese health-care system is not well equipped to support successful implementation of risk-sharing arrangements.…”
Section: Discussionmentioning
confidence: 99%
“…To control the government’s expenditure, risk-sharing arrangements can be introduced when these innovative medicines are included on the National Reimbursement Drug List, and real-world evidence can be used to monitor the medicines’ cost–effectiveness. 33 , 34 If a targeted medicine has no meaningful clinical benefits compared with essential medicines, clinical guidelines should recommend use of the latter over the former. Currently, the Chinese health-care system is not well equipped to support successful implementation of risk-sharing arrangements.…”
Section: Discussionmentioning
confidence: 99%
“…USA Palanisamy & Thirunavukarasu [45] Implications of big data analytics in developing healthcare frameworks-A review. India Pisana [46] Challenges and opportunities with routinely collected data on the utilization of cancer medicines: Perspectives from health authority personnel across 18 European countries. Sweden Qian [47] Multi-label feature selection based on information entropy fusion in multi-source decision system.…”
Section: Resultsmentioning
confidence: 99%
“…The higher cost of cancer medicines, the type of national public insurance schemes, and the non-availability of the facilities are the main established barriers to therapy access (22). Funding of oncology medicines is nationally regulated both for outpatient and hospital treatments (23). The studies reported substantial differences in anticancer medicines included in the Essential Medicines List, availability in private and public hospitals, and the level of reimbursement (24,25).…”
Section: Discussionmentioning
confidence: 99%